Grupo de Teatro Popular de Sansinena. Nuevos abordajes posibles para su análisis - Fernández, Clarisa (Latin American Theatre Review, 2013)
This article presents a series of reflections on Argentine community theatre. An examination of Sansinena’s Popular Theatre Group will analyze the strengths and conceptual limitations of this collective experience and address categories of community experience constructed mainly in the field of cultural studies. This includes a consideration of works from social movements, as well as different ways of understanding the dialogue that occurs between “political” and collective action. The article will also take into account the characteristics of the rural territory in which the practice of community theatre takes place and the influence of those characteristics on theatrical production and collective experience.